Knowledge Management Barriers in the Brazilian Energy Sector - Gouveia, Amanda; Gonçalves, Antonio Augusto; Sabbadini, Francisco Santos; Barbosa, José Geraldo Pereira (Revista Valore, 2023)
Paper aims: Nowadays, there are happening profoundly changes in the energy sector worldwide. The principal innovations are sustainability, the growing share of renewable energy sources, and energy efficiency. Knowledge Management (KM) is a critical process in energy companies. KM implementation is harmfully affected by factors known as KM barriers. This paper aims to identify those barriers. Originality: Knowledge management is fundamental to most organizations’ strategy and operations in the energy sector. However, the energy companies need to overcome KM barriers. These issues are rarely addressed in the literature. Research method: This empirical, theoretical study is a qualitative approach, descriptive and exploratory. The research adopts the single case study method, having semi-structured interviews and participant observation to identify KM barriers. Main findings: Results demonstrate that the lack of incentive from top management, lack of motivation for sharing, staff retention hardship, and focusing merely on operations efficiency was identified as the main barriers to develop KM. Implications for theory and practice: These perspectives have not been explored yet and shall open a new approach to knowledge management implementation in energy companies. It offers practical guidance for diffusing and deploying KM initiatives in the energy sector.